SISTEM INFORMASI GEOGRAFIS BERBASIS WEB PERSEBARAN TEMPAT PEMBUANGAN SEMENTARA KOTA TEMBILAHAN - Arkadius, Dio Julian; Iswahyudi, Ardian; Saputra, Dimas Aryo; Amrullah, Muhammad Alim (TEKNOFILE : Jurnal Sistem Informasi, 2025)
The Geographic Information System (GIS) has excellent capabilities in visualizing spatial data along with its attributes, modifying shapes, colors, sizes, and symbols. This technological advancement can be utilized to manage waste in a way that supports environmental sustainability. According to records from the Environmental and Sanitation Department (DLHK) of Tembilahan, there are 50 tons of waste generated daily in the Tembilahan and Tembilahan Hulu areas. Waste management in Tembilahan city is still not optimal, as many Temporary Disposal Sites (TPS) are not yet known by residents in their respective areas, leading to waste being dumped along roadsides near their homes. Through technological developments, a mapping system for TPS waste disposal locations has been developed using GIS. This system aims to help the public access information about the nearest TPS locations, the waste collection schedule from TPS to the final disposal site (TPA), based on mobile phone coordinates and residential address search. The system is developed using the Waterfall method. With this system, both the community and the Environmental and Sanitation Department of Tembilahan can monitor TPS locations and provide information on waste collection in each sub-district through a website-based system utilizing GIS.